APLIKASI LIMBAH SIMAUANG, CANGKANG TELUR, DAN BONGGOL JAGUNG KEPADA AKSESORIS RUANG - FITRIA MELSA, Drs. Erwin A, M.Sn., Dra. Jupriani, M.Sn. (Serupa The Journal of Art Education, 2016)
Waste is something useless and discarded by most people. They regard it as something useless. If left too long will couse disease. Whereas processing correctly will make waste into economically valuable. The emergence of this idea came from the author’s observation of the waste that has not been explored, thus inspiring the creation of works this thesis. In the embodiment of the author’s work adopts the form of accessories existing spase to be used as a three-dimensional works. The concept of embodiment of this thesis is the utilization of household waste into spase accessories that become object of aesthetic value and economic. Simauang (pangium edulle 2reinw), egg shells and corn stalks that have not been conserved up to the author a body accsessories pottery, flower pots, ornaments and others audut.Through the mosaic technique (patch) the authors suggest to the craftmen’s creative use of waste, to make it more marketable, beautifull and fun.Keyworks: Limbah, teknik mozaik (tempelan), aksesoris, ruangan